Performance Evaluation of Carbon‐Based Printed Perovskite Solar Cells under Low‐Light Intensity Conditions. Issue 10 (21st October 2022) - Kim, Cuc Mai Thi; Perera, Malalgodage Amila Nilantha; Katz, Marcos; Martineau, David; Hashmi, Syed Ghufran
Abstract : The cover image highlights the work reported by Syed Ghufran Hashmi and co‐worker, article number 2200747, which includes the performance evaluation and the efficient working of a temperature sensing node by harvesting low lux light energy through this low cost, printable and efficient solar cell technology.